An efficient spur gear shaping method based on homogenizing cutting area through variational circular feed rate. (July 2017) - Li, Linqing; Zhang, Lianhong; Yu, Bing; Wang, Kaifeng; Liu, Fucong
Gear shaping is a widely applied technology to produce spur gears. Generally, the pinion cutter and the gear workpiece rotate uniformly with a given gear ratio during the conventional gear shaping process, which can cause a large variation of the cutting area per stroke in cutting tooth spaces. It makes the cutting force less than the rated capacity of the gear shaper in most cutting strokes and thus reduces the process efficiency. To overcome such a shortage, a new spur gear shaping method is proposed in this article, in which the cutting area per stroke is homogenized to a target value through optimizing the circular feed rate. The new method can enhance process efficiency by keeping the cutting force equivalent to the rated capacity of the gear shaper. The specific algorithm includes a number of aspects: cutting area calculation, gear profile generation, cutting area analysis of conventional gear shaping, and cutting area homogenization. Additionally, the new spur gear shaping method is demonstrated and validated using a VERICUT simulation. From the simulation results, it is found that the process efficiency is improved up to 40% via the efficient gear shaping because of the reduced number of shaping strokes. Hence, the new spur gear shaping method is applicable for computer numerical control gear shapers to improve the process efficiency significantly without any additional hardware changes.